Growth portfolios buffer climate‐linked environmental change in marine systems. Issue 3 (11th January 2023) - Campana, Steven E.; Smoliński, Szymon; Black, Bryan A.; Morrongiello, John R.; Alexandroff, Stella J.; Andersson, Carin; Bogstad, Bjarte; Butler, Paul G.; Denechaud, Côme; Frank, David C.; Geffen, Audrey J.; Godiksen, Jane Aanestad; et al.
Abstract: Large‐scale, climate‐induced synchrony in the productivity of fish populations is becoming more pronounced in the world's oceans. As synchrony increases, a population's "portfolio" of responses can be diminished, in turn reducing its resilience to strong perturbation. Here we argue that the costs and benefits of trait synchronization, such as the expression of growth rate, are context dependent. Contrary to prevailing views, synchrony among individuals could actually be beneficial for populations if growth synchrony increases during favorable conditions, and then declines under poor conditions when a broader portfolio of responses could be useful. Importantly, growth synchrony among individuals within populations has seldom been measured, despite well‐documented evidence of synchrony across populations. Here, we used century‐scale time series of annual otolith growth to test for changes in growth synchronization among individuals within multiple populations of a marine keystone species (Atlantic cod, Gadus morhua ). On the basis of 74, 662 annual growth increments recorded in 13, 749 otoliths, we detected a rising conformity in long‐term growth rates within five northeast Atlantic cod populations in response to both favorable growth conditions and a large‐scale, multidecadal mode of climate variability similar to the East Atlantic Pattern. The within‐population synchrony was distinct from the across‐population synchrony commonly reported for large‐scale environmental drivers. Climate‐linked, among‐individual growth synchrony was also identified in other Northeast Atlantic pelagic, deep‐sea and bivalve species. We hypothesize that growth synchrony in good years and growth asynchrony in poorer years reflects adaptive trait optimization and bet hedging, respectively, that could confer an unexpected, but pervasive and stabilizing, impact on marine population productivity in response to large‐scale environmental change.